Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22158315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ganglioside Receptor Recognition by Botulinum Neurotoxin Serotype E

Abstract: The botulinum neurotoxins are potent molecules that are not only responsible for the lethal paralytic disease botulism, but have also been harnessed for therapeutic uses in the treatment of an increasing number of chronic neurological and neuromuscular disorders, in addition to cosmetic applications. The toxins act at the cholinergic nerve terminals thanks to an efficient and specific mechanism of cell recognition which is based on a dual receptor system that involves gangliosides and protein receptors. Bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…This finding is also consistent with the structure of H C E–ganglioside complex that was published during the preparation of this manuscript (Fig. 1d ) 48 . Furthermore, we previously reported that mutating H C E-W1224 was sufficient to abolish its ganglioside binding 26 , 28 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is also consistent with the structure of H C E–ganglioside complex that was published during the preparation of this manuscript (Fig. 1d ) 48 . Furthermore, we previously reported that mutating H C E-W1224 was sufficient to abolish its ganglioside binding 26 , 28 .…”
Section: Resultssupporting
confidence: 92%
“…We found that the structure of the G6-bound H C E is virtually identical to that in complex with GD1a (root mean square deviation, r.m.s.d. ~0.38 Å over 359 aligned Cα pairs) 48 . Therefore, we hypothesized that G6 could be used as a ganglioside surrogate to facilitate SV2A binding to H C E when G6 and SV2A are properly connected with a flexible peptide linker because such a fusion protein would allow synergistic binding of G6 and SV2A to H C E in a way resembling the dual receptor binding.…”
Section: Resultsmentioning
confidence: 99%
“…Serotypes A, B and E are the main BoNT associated with human botulism [5]. These neurotoxins specifically target presynaptic motoneurons via a dual-receptor binding mechanism, which involves membrane-anchored gangliosides [6][7][8] and a protein receptor [9]. BoNT/A, /D, /E and /F recognise the synaptic vesicle glycoprotein 2 (SV2), whereas BoNT/B, /G and /DC utilise one of the synaptotagmin isoforms [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the stretch SXWY is the conserved ganglioside binding site (GBS) and has been identified first in tetanus neurotoxin as well as in BoNT/A, B, E, F, and G [39][40][41]. Interestingly, in E1 GBS, key interacting residues that are unique to BoNT/E have been identified along with a significant rearrangement of loop 1228-1237 upon carbohydrate binding [42]. In BoNT/B, the LBL is located between the GBS and the receptor binding site, and is significantly exposed to the solvent, in particular the sidechains of W 1248 and W 1249 [43].…”
Section: Flexibility Of the Lipid-binding And Ganglioside-binding Dom...mentioning
confidence: 99%